(untitled) (Journal of Applied Learning and Teaching, 2021)
Feedback is integral to the process of education but is not a simple process and in mass education and global systems presents numerous additional challenges. This paper, which is intended as an informative awareness-raising paper, provides a review of recent literature on the challenges that educators and students face when feedback is given and received. It conceptualizes feedback as a process that requires multiple inputs and should support the partnership between educators and students through dialogue and engagement. Feedback literacy that incorporates the role of emotion is seen as a key aspect of professional and student development to motivate and engage students.